2018
DOI: 10.1111/jora.12433
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Adolescents’ Neural Processing of Self, Friends, and Teachers: Consequences for the School Self‐Concept

Abstract: The present interdisciplinary study explored whether perceived loneliness is associated with ventromedial prefrontal cortex (vMPFC) activation during self- and social judgments (friends and teachers) in adolescents. Moreover, we examined how vMPFC activity is related to the academic self-concept (ASC). Results of manifest path analysis indicated that high perceived loneliness was related to lower neural response to self-judgments. In turn, high neural response to self-judgments was positively associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 103 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…Twenty-four studies focused on younger adults (mean age 18–60; [ 24 47 ]), 12 on older adults (mean age >60; [ 48 59 ]), two on adolescents [ 60 , 61 ], and two across the lifespan [ 62 , 63 ]. Most reports included healthy individuals while seven focused on clinical populations: four with depression [ 47 , 49 , 51 , 57 ], and one each with traumatic brain injury (TBI) [ 58 ], schizophrenia [ 28 ], and severe hearing impairment [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-four studies focused on younger adults (mean age 18–60; [ 24 47 ]), 12 on older adults (mean age >60; [ 48 59 ]), two on adolescents [ 60 , 61 ], and two across the lifespan [ 62 , 63 ]. Most reports included healthy individuals while seven focused on clinical populations: four with depression [ 47 , 49 , 51 , 57 ], and one each with traumatic brain injury (TBI) [ 58 ], schizophrenia [ 28 ], and severe hearing impairment [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen reports analyzed the relationship between loneliness and brain function or connectivity using fMRI. Ten of these studies were task-based ( n = 10; [ 24 , 25 , 28 , 34 , 44 , 45 , 51 , 60 , 62 , 63 ]), and two were resting-state fMRI ( n = 8; [ 37 , 39 43 , 47 , 49 ]) (Table 2 ). One report appears in both Tables 1 and 2 [ 63 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, teachers give frequent feedback-consciously and unconsciously-with respect to a student's behavior and school performance, communicating their approval to the student (Hattie and Timperley, 2007), which, in turn, may be associated with student's self-worth. This argument is supported by a neurobiological study which found that during an fMRI task, teacher appraisals, but not peer or self-referential appraisals, were linked to students' academic self-concept (Golde et al, 2019). In fact, studies indicate that how students evaluate their abilities and themselves as people depends in part on the support and feedback of their teachers (Möller and Köller, 2001a,b;Skaalvik and Skaalvik, 2002;Möller et al, 2009;.…”
Section: Discussionmentioning
confidence: 97%